A linear scaling law for predicting phase transition temperature via averaged effective electronegativity derived from A2M3O12-based compounds. Issue 9 (29th July 2021) - Yuan, Huanli; Wang, Chunyan; Gao, Qilong; Zeng, Gaojie; Guo, Juan; Chao, Mingju; Kawaguchi, Shogo; Jia, Yu; Liang, Erjun
Abstract : A2 M3 O12 -based compounds exhibit NTE properties only after phase transition from the monoclinic to the orthorhombic. The linear scaling law of averaged effective electronegativity (AEE) can be used to predict phase transition temperature ( T t ). Abstract : The chemical flexibility of A2 M3 O12 -based compounds enables the design of materials with versatile functionalities such as ferroelastic switching, ion conduction and negative thermal expansion (NTE) above the ferroelastic transition temperature ( T t ), which is promising for a variety of applications. Quantitative prediction of T t is essential but lacking. Herein we propose a concept of averaged effective electronegativity (AEE) and establish a linear relationship between the T t and AEE for A2 M3 O12 -based compounds. The linear scaling law is validated using first principles calculations of the effective charge on oxygen and its effectiveness is verified experimentally by designing high entropy compounds Sc x 1 Zr x 2 Hf x 3 Fe x 4 Mo y 1 V y 2 O12 and a NTE compound Zr2 MoVPO12 with expected T t . Generalization of the linear scaling law to other NTE oxides with displacive phase transition is also demonstrated. The findings can be used as a simple and effective approach to guide the design of novel compounds with desired properties and T t .